2018
DOI: 10.1017/s0014479718000443
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal inoculation and application of cattle manure in field-grown maize in semiarid conditions

Abstract: We evaluated the effects of cattle manure and inoculation with arbuscular mycorrhizal fungi (AMF) in maize plants growing in a semiarid area of Brazilian north-east in 2012 and 2013. Three isolates of AMF (Acaulosporalongula URM-FMA 07 and URM-FMA 03, Claroideoglomusetunicatum UNIVASF 06A) were used, with or without the application of cattle manure, during two growing cycles. In the first year, significant effects of inoculation were detected for straw yield only when the manure was applied. In the second year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…---spore 100 g-1 soil -----------% -------- In a field experiment, Lino et al ( 2018) also found higher percentages of mycorrhizal colonization in corn roots that had been inoculated at sowing with Acaulospora longula and Claroideoglomus etunicatum (= Entrophospora etunicata) (mean of 72%) compared to non-inoculated ones (mean of 54%). Although mycorrhizal colonization in inoculated plants, both in our study and in Lino et al (2018), was higher than in non-inoculated plants, it is not possible to attribute these percentages to the inoculum used, since the technique used to evaluate mycorrhizal colonization does not allow the identification of the AMF inoculated. In addition, AMF species from the native community can colonize the roots of these plant species, as observed by the percentages found in non-inoculated plants.…”
Section: Spore Density Mycorrhizal Colonizationcontrasting
confidence: 63%
“…---spore 100 g-1 soil -----------% -------- In a field experiment, Lino et al ( 2018) also found higher percentages of mycorrhizal colonization in corn roots that had been inoculated at sowing with Acaulospora longula and Claroideoglomus etunicatum (= Entrophospora etunicata) (mean of 72%) compared to non-inoculated ones (mean of 54%). Although mycorrhizal colonization in inoculated plants, both in our study and in Lino et al (2018), was higher than in non-inoculated plants, it is not possible to attribute these percentages to the inoculum used, since the technique used to evaluate mycorrhizal colonization does not allow the identification of the AMF inoculated. In addition, AMF species from the native community can colonize the roots of these plant species, as observed by the percentages found in non-inoculated plants.…”
Section: Spore Density Mycorrhizal Colonizationcontrasting
confidence: 63%
“…Nutrient uptake (p) Increased -N; P; K; Ca; Mg; Na [37,186,[207][208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223] Nutrient uptake (f) Increased -P; K; Ca; Mg; Fe [221,[224][225][226] Vegetative growth (p) Increased -shoot and root biomass; root length; plant, leaf and tassel length; stem girth [186, 203, 205, 206-209, 211, 213, 214, 216, 219, 221-229] Vegetative growth (f) Increased -shoot and root biomass; root length; plant height; leaf mass and area [217,221,224,226,[230][231][232][233][234] Yield (p) Increased -cob and grain yield; number of grains per cob [215,221,[235][236][237] Yield [86,266], while for glomalin, it varies from 6 to 42 years [120]. The effects of AM fungi on soil aggregation are probably more easily detected in nutrient-poor soils with neutral or alkaline soil pH [268].…”
Section: Parameter (P/f) * Benefits Referencementioning
confidence: 99%